Small worlds, global lives : islands and migration - King, Russell 1945-; Connell, John 1946- (Island studies series, 1999)
As "small worlds", where resources are often stretched, islands have had an intense experience of migration. For many small islands in a global era, migration represents a dialogue between different places, some urban, some rural. This book examines diverse facets of migration out of and into a variety of islands, from the North Atlantic to the South Pacific. It traces the way in which migration is of crucial importance, for demography, economics, culture, indeed the whole of island life and identity; it contrasts with the reality of emigration and the rhetoric of return. Topics explored include include migration and environmental change, language shifts, remittances, retirement migration, post-colonial identities and islanders on the Internet. The evidence shows that migration emerges our of islanders' needs, but inevitably transforms insular societies, changing values and expectations, yet rarely if ever contributing to a situation where it is no longer necessary.